Psychosocial Safety Climate and WorkRelated Outcomes in Malaysian Research Universities: The Role of Job Demands - Gan, Kia Hui; Kee, Daisy Mui Hung (International Journal of Psychosocial Rehabilitation, 2020)
Recently the ranking Malaysian research universities have been improving in QS World University Ranking, especially Universiti Malaya. To continue to improve in the ranking, Malaysia Research Assessment (MyRA) came out with their expectation of academicians. To ensure academicians to achieve MyRA’s expectation, management of research universities insert these expectations in academicians’ key performance index (KPI) as well. These expectations are overloaded for academicians. Thus, the work-related outcomes in this study will be included work engagement and job satisfaction among academician is decreasing in Malaysian research universities. The present study aims to improve the work-related outcomes of academicians by applying Psychosocial Safety Climate (PSC) in their university policy. PSC context suggested for university management to revise the university's policy which can protect academicians' psychological health and safety. A healthy working environment can help to enhance academicians' performance as well. Hence, PSC is a precious method to assist the university management team and policymaker to improve academicians’ work-related outcomes.